2018
DOI: 10.1111/acer.13936
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal from Brief Repeated Alcohol Treatment in Adolescent and Adult Male and Female Rats

Abstract: Background: Early initiation of alcohol drinking has been associated with increased risk of alcohol dependence in adulthood. Although negative affect mediated in part by corticotropinreleasing factor (CRF) is a strong motivator for alcohol consumption in adults, comparisons of alcohol withdrawal in adolescents and adults generally have not included CRF-related measures like anxiety. The purpose of the present study was to compare withdrawal signs including anxietylike behavior after a brief multi-day alcohol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The majority of the studies performed either with rats (117)(118)(119)(120)(121)(122)(123) or mice (63, [124][125][126][127][128][129][130] have failed to show sex-differences in this test. In some of these studies direct comparisons among strains (97,131,132) and/or age of the animals (133,134), which are critically-relevant variables, were performed but no sex-related effect was found. There are however, a few reports showing that females are more (135)(136)(137)(138) or less (139)(140)(141)(142)(143) anxious than males.…”
Section: Light-dark Transition Testmentioning
confidence: 99%
“…The majority of the studies performed either with rats (117)(118)(119)(120)(121)(122)(123) or mice (63, [124][125][126][127][128][129][130] have failed to show sex-differences in this test. In some of these studies direct comparisons among strains (97,131,132) and/or age of the animals (133,134), which are critically-relevant variables, were performed but no sex-related effect was found. There are however, a few reports showing that females are more (135)(136)(137)(138) or less (139)(140)(141)(142)(143) anxious than males.…”
Section: Light-dark Transition Testmentioning
confidence: 99%
“…Chronic exposure to alcohol and other drugs of abuse causes long-term changes in reward processing that are thought to promote a continued escalation of substance use. Even though positive hedonic feelings occur shortly after the drug intake, negative hedonic responses follow-especially after repeated exposures-due to alterations in the brain reward system and stress-related structures such as the extended amygdala, resulting in a withdrawal syndrome including dysphoria, irritability, anxiety, and other negative emotional states (Zhang and Schulteis, 2008;Leventhal et al, 2013;Su et al, 2017;Fleming et al, 2019). Some hypothesize that over time the desire to avoid the negative feelings associated with withdrawal becomes the primary motivational factor for compulsive drug-seeking behavior (Solomon and Corbit, 1974;Koob and Volkow, 2010).…”
Section: Overlapping Effects Of Trauma and Drugs On Neuronal And Endomentioning
confidence: 99%
“…As with preclinical research on sex differences in relation to EtOH drinking, there is also a paucity of preclinical research on sex differences in relation to affective behavior. In regard to exploratory and anxiety-like behavior, most research has been conducted in Wistar and Sprague-Dawley rats, and has found that females compared to males show greater horizontal and vertical (rearing) activity in a novel chamber (Hughes & Hancock, 2016;Kokras et al, 2020), greater or no difference in time in the light chamber of a light-dark box (De Oliveira Sergio et al, 2021;Fleming et al, 2019;Kokras et al, 2020), and more hole exploration in a hole board apparatus (Kokras et al, 2020;Ray & Hansen, 2004). One study has probed the sexdependent effects of EtOH on behavior in a light-dark box, using experimenter-administered EtOH, and found that this EtOH reduced to an equal extent time spent in the light chamber, entries into the light chamber, and overall ambulatory activity in male and female rats (Fleming et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to exploratory and anxiety‐like behavior, most research has been conducted in Wistar and Sprague‐Dawley rats, and has found that females compared to males show greater horizontal and vertical (rearing) activity in a novel chamber (Hughes & Hancock, 2016; Kokras et al, 2020), greater or no difference in time in the light chamber of a light–dark box (De Oliveira Sergio et al, 2021; Fleming et al, 2019; Kokras et al, 2020), and more hole exploration in a hole board apparatus (Kokras et al, 2020; Ray & Hansen, 2004). One study has probed the sex‐dependent effects of EtOH on behavior in a light–dark box, using experimenter‐administered EtOH, and found that this EtOH reduced to an equal extent time spent in the light chamber, entries into the light chamber, and overall ambulatory activity in male and female rats (Fleming et al, 2019). To our knowledge, no such investigations of sex‐dependent effects of EtOH have been made of behavior in a novel chamber or hole board apparatus nor has exploratory behavior after voluntary EtOH drinking been examined.…”
Section: Introductionmentioning
confidence: 99%